2011
DOI: 10.1371/journal.pone.0018111
|View full text |Cite
|
Sign up to set email alerts
|

Combined Evaluation of FDG-PET and MRI Improves Detection and Differentiation of Dementia

Abstract: IntroductionVarious biomarkers have been reported in recent literature regarding imaging abnormalities in different types of dementia. These biomarkers have helped to significantly improve early detection and also differentiation of various dementia syndromes. In this study, we systematically applied whole-brain and region-of-interest (ROI) based support vector machine classification separately and on combined information from different imaging modalities to improve the detection and differentiation of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
126
1
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(146 citation statements)
references
References 37 publications
(50 reference statements)
12
126
1
7
Order By: Relevance
“…Figure 2 shows a representative case of frontotemporal dementia with concordant PET and MRI data. This finding is consistent with previous literature data [35,36].…”
Section: Neurodegenerative and Cerebrovascular Disorderssupporting
confidence: 94%
“…Figure 2 shows a representative case of frontotemporal dementia with concordant PET and MRI data. This finding is consistent with previous literature data [35,36].…”
Section: Neurodegenerative and Cerebrovascular Disorderssupporting
confidence: 94%
“…The classification accuracies in our study are generally consistent with prior studies using FDG‐PET, which have achieved accuracy rates of around 80–95%. However, it should be noted that most prior studies assessing classification accuracy in FTLD have used a mixed group of FTLD cases, including cases with the semantic and nonfluent variants of primary progressive aphasia (the exception is the European study referenced above12, 50). Therefore, direct comparison of our classification outcomes with those of prior studies must be done with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of bvFTD remains difficult, with patients being erroneously diagnosed with Alzheimer's disease (AD) or psychiatric disorders 5, 6, 7. A large body of work has demonstrated that brain imaging, in particular structural magnetic resonance imaging (MRI) and functional imaging of cerebral blood flow (CBF) with SPECT or cerebral metabolic rate of glucose (CMRgl) with fluorodeoxyglucose (FDG) positron emission tomography (PET), can improve the accuracy of differential diagnosis in bvFTD 8, 9, 10, 11, 12, 13, 14, 15, 16, 17. These findings led the Center for Medicare and Medicaid Services (CMS) to approve FDG‐PET as a diagnostic test for differentiating bvFTD from AD (https://www.cms.gov/medicare-coverage-database/details/ncd-details.aspx?NCDId=288&ncdver=3&bc=BAABAAAAAAAA&).…”
Section: Introductionmentioning
confidence: 99%
“…For example, 18 F-FDG PET and structural MRI, respectively, detect regional hypometabolism, which reflects lowered regional neural activity, and atrophy, which reflects neurodegeneration, and both procedures are used for individual diagnostics (17)(18)(19). Restingstate functional MRI (rs-fMRI) facilitates the measurement of coherent ongoing brain activity, which reflects patterns of intrinsic functional connectivity including those of intrinsic brain networks (8,20).…”
mentioning
confidence: 99%